2021
DOI: 10.5812/jjcmb.115348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical Composition of Hamadan Propolis as a Potential Anticancer Agent

Abstract: : This study aimed to evaluate the chemical composition and anticancer activity of Hamadan propolis essential oil and methanolic extract on HCT116 cell line. The anticancer activity of propolis methanolic extract and essential oil was evaluated by using the MTT (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide) test on the colorectal HCT116 cell line. The essential oil of Hamadan propolis was analyzed by gas chromatography-flame ionization detection (GC-FID) and gas chromatography-mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
0
2
Order By: Relevance
“…Recently, Fang, Xiong, Xu, Yin, and Luo [ 37 ] reported the proapoptotic activity of polyphenolic compounds such as ferulic acid and caffeic acid on human tongue squamous carcinoma cells (CAL-27). Current results were higher than the findings of Dastan et al [ 22 ] who reported propolis methanolic extracts with ( IC 50 ) 702.5 and 177.7 μ g mL −1 after 24 and 48 hours.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Recently, Fang, Xiong, Xu, Yin, and Luo [ 37 ] reported the proapoptotic activity of polyphenolic compounds such as ferulic acid and caffeic acid on human tongue squamous carcinoma cells (CAL-27). Current results were higher than the findings of Dastan et al [ 22 ] who reported propolis methanolic extracts with ( IC 50 ) 702.5 and 177.7 μ g mL −1 after 24 and 48 hours.…”
Section: Discussioncontrasting
confidence: 87%
“…The propolis extract (P1) collected from Ziarat region expressed maximum flavonoid content (0.6586 ± 0.329) and the extract (P6) from Bela region have the lowest content (0.1546 ± 0.087) mg of quercetin g −1 of propolis extract presented in ( Table 2 ). Results of current study are minimum than other reported studies from different location in Turkey [ 3 ], Pakistan [ 1 ], China [ 21 ], and Iran [ 22 ]. According to Choi et al [ 20 ], the variations in total phenolic and total flavonoids of propolis samples depend on their geographic origin.…”
Section: Discussioncontrasting
confidence: 84%